Uncovering Consciousness and Revealing the Preservation of Mental Life in Unresponsive Brain-Injured Patients - Naci, Lorina; Owen, Adrian M. (Seminars in Neurology, 2022)
In the last few years, functional neuroimaging and electroencephalography-based techniques have been used to address one of the most complex and challenging questions in clinical medicine, that of detecting covert awareness in behaviorally unresponsive patients who have survived severe brain injuries. This is a very diverse population with a wide range of etiologies and comorbidities, as well as variable cognitive and behavioral abilities, which render accurate diagnosis extremely challenging. These studies have shown that some chronic behaviorally unresponsive patients harbor not only covert consciousness but also highly preserved levels of mental life. Building on this work, although in its infancy, the investigation of covert consciousness in acutely brain-injured patients could have profound implications for patient prognosis, treatment, and decisions regarding withdrawal of care. The body of evidence on covert awareness presents a moral imperative to redouble our efforts for improving the quality of life and standard of care for all brain-injured patients with disorders of consciousness.
Keywords: covert consciousness; brain injury; mental life